Role of Nucleosides on Nickel Electroplating from a Formamide Bath (Biological Sciences - PJSIR, 2006)
The outwardly growth mechanism during electrocrystallization results in appreciable thickness and reflectivity, whereas lateral growth leads to thin and inferior reflectivity. Outward growth deposits essentially depend upon the operating conditions. They also depend upon the release of cations in the catholyte from the metal-non-aqueous complex. The nucleoside additive has a large number of coordinating centres for complexation. In formamide medium, the availability of large number of such centres leads to better electrodepostion than those additives having a lesser number. Deoxyguanosine, having a maximum number of coordinating centres, and “N” and “O”, leads to electrodeposits having no peeling effect and better reflectivity. However, this peeling effect diminishes if a comparatively large concentration of nucleosides is used. The presence of nucleosides in a non-aqueous electroplating bath not only improves the quality of electrodeposits but improves the thickness too.